Organocatalysts Effect on the Stereoselectivity of [2, 3]‐Wittig Rearrangement. Issue 2 (15th January 2019) - Peňaška, Tibor; Mojzes, Melinda Meyer; Filo, Juraj; Jurdáková, Helena; Mečiarová, Mária; Šebesta, Radovan
Abstract : The organocatalytic [2, 3]‐Wittig rearrangement of allyloxyketones was investigated. Extensive screening of chiral amine organocatalysts showed that small pyrrolidine‐based catalysts or simple phenylethylamine with the primary amino group were the most effective ones. Interestingly, CF3 ‐derived pyrrolidine affords the rearrangement product with an opposite absolute configuration to the product obtained by using the corresponding non‐fluorinated proline derived catalysts. Mechanistic and computational investigations were also performed. Abstract : A range of amine organocatalysts were screened in the [2, 3]‐Wittig rearrangement of allyloxyketones. Sterically unencumbered catalysts, such as phenylethylamine or small pyrrolidine derivatives, seem to be preferred for this reaction. Intermediates of the reaction were observed by NMR and MS. ( Z )‐Configured enamines are preferred ones based on DFT calculations.